Not guilty? Another look at the nature and nurture of economics students - Justus Haucap; Tobias Just (Deutsche Bank Research, 2003)
Economists praise the efficiency of the price mechanism in allocating scarce resources. Others, however, often reject it as unfair. In this study, we investigate the extent to which economists also differ from non-economists in how they value the fairness of the price system, and examine how deeply such differences are rooted in their course of studies. The result: studying economics does in fact influence how they arrive at value judgements, though students' attitudes do not stem solely from this factor - their views already differ from those of non-economics students right at the beginning of their studies.
Keywords: A12; A13; A20; D63; 330; Economists; fairness; learning; selection; attitudes; Wirtschaftswissenschaftler; Gerechtigkeit; Marktmechanismus; Allokation; Schätzung; Meinung; Deutschland